2010
DOI: 10.1093/nar/gkp1191
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the induction mechanism of the GntR/HutC bacterial transcription regulator YvoA

Abstract: YvoA is a GntR/HutC transcription regulator from Bacillus subtilis implicated in the regulation of genes from the N-acetylglucosamine-degrading pathway. Its 2.4-Å crystal structure reveals a homodimeric assembly with each monomer displaying a two-domain fold. The C-terminal domain, which binds the effector N-acetylglucosamine-6-phosphate, adopts a chorismate lyase fold, whereas the N-terminal domain contains a winged helix–turn–helix DNA-binding domain. Isothermal titration calorimetry and site-directed mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
98
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(111 citation statements)
references
References 49 publications
(84 reference statements)
12
98
1
Order By: Relevance
“…However, Resch and collaborators demonstrated that once bound to GlcNAc-6-P, NagR is still able to bind half-side dre in vitro. This is compatible with a model in which the regulator acts as both an activator and a repressor beyond the canonical mutually exclusive effector-bound or DNA-bound regulator logic (49). If GlcNAc-6-P should prove capable of inducing a jumping-jacklike motion of NagR (as proposed by Resch et al) in vivo or if the NagR/GlcNAc-6-P complex is still able to recognize and bind half-side dre, this automatically raises the question of how widespread the distribution of half-NagR-binding sites in the B. subtilis chromosome is.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…However, Resch and collaborators demonstrated that once bound to GlcNAc-6-P, NagR is still able to bind half-side dre in vitro. This is compatible with a model in which the regulator acts as both an activator and a repressor beyond the canonical mutually exclusive effector-bound or DNA-bound regulator logic (49). If GlcNAc-6-P should prove capable of inducing a jumping-jacklike motion of NagR (as proposed by Resch et al) in vivo or if the NagR/GlcNAc-6-P complex is still able to recognize and bind half-side dre, this automatically raises the question of how widespread the distribution of half-NagR-binding sites in the B. subtilis chromosome is.…”
Section: Resultssupporting
confidence: 79%
“…3A). GlcN-6-P was also reported to inhibit the DNA-binding capability of DasR in S. coelicolor (51), whereas isothermal calorimetry titration measurements for binding of GlcN-6-P to YvoA conducted by Resch and colleagues had been inconclusive (49). Interestingly, the crystal structure in this study had been solved for YvoA in complex with GlcNAc-6-P, which had not appeared to interfere with dre binding in EMSA.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…EMSAs performed with DasR of Saccharopolyspora erythraea (DasR sery ) also revealed that GlcN-6P was able to modulate its DNA-binding capability though in a different way than the simple dissociation of the regulatory protein from its target dre observed for DasR of S. coelicolor (DasR sco ) as, instead, multiple retarded bands were observed upon incubation of DasR sery with GlcN-6P [6]. In Bacilli, the GntR/HutC family NagR (formerly named YvoA [16]) is the DasR orthologue which appears to only control genes for GlcNAc transport and phosphorylation by the PTS (nagP), and the genes for its subsequent deacetylation into GlcN-6P (nagA), and GlcN-6P deamination and isomerization into fructose-6-phosphate (nagB) [17]. The first attempt to identify the allosteric effector of NagR revealed a similar inhibitory effect of GlcN-6P on the DNA-binding ability of NagR as described for DasR sco [17].…”
Section: Introductionmentioning
confidence: 98%
“…When GlcNAc is present in the environment, intracellular GlcNAc-6-P accumulates and activates the expression of genes for GlcNAc and GlcN catabolism by disrupting the interaction between NagC and dre sites (5,(11)(12)(13). In the Gram-positive bacterium Bacillus subtilis, a GntR/HutC-type regulator, designated NagR (formerly YvoA), binds to nonhomologous operator sites, also called dre (14,15), to control the transcription of nagA, nagB, and nagP, which codes for a GlcNAc-specific PTS permease. Unlike in E. coli, though, the allosteric effector(s) that alleviates repression of these target genes by NagR remains undetermined (14,16,17).…”
mentioning
confidence: 99%